Incidence of lung cancer and mortality among civil construction industry workers: A protocol for a systematic review and meta-analysis - Cahuana Pinto, Rita Stella Maria (2021)
The construction sector is one of the most stable growth industries in the world. However, many studies have suggested an association between occupational exposure in civil construction and lung cancer risk. Thus, this study aims to assess lung cancer risk in civil construction workers occupationally exposed to physical and chemical agents through a systematic review and meta-analysis.